The effects of sonification on interpretation of geo-visualization of complex dengue data - Lee, Lilian Yen Wei (2018)
The effective way for analysing complex data sets, it’s the ability to represent the overall pattern of data in a single presentation by providing alternative input options. While vast of work for data mapping focusing on visual presentations, the work of this thesis suggest that data sonification can be better aids towards complex data interpretation especially when comes to complement visual representation. In this project, an ambient sound framework was designed so it can be applied to display complex dengue data. Parameter mapping method was applied to filter data with temporal factor and represent it with sound parameters. Four sound parameters were used: onset, volume, pitch and tempo. A simulation prototype was developed using open source JavaScript library: leaflet map, leaflet timeline and audiosynth.js. Data collected from experiment through task assessment were analysed using PASW. Results from the tested framework shows that there is positive significance statistic difference in the level of data interpretation when sound was used for complex dengue data representation.